2011
DOI: 10.1155/2011/639814
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Use and Self-Reported Symptoms of Acute Pesticide Poisoning among Aquatic Farmers in Phnom Penh, Cambodia

Abstract: Organophosphates and carbamates (OPs/CMs) are known for their acetylcholinesterase inhibiting character. A cross-sectional study of pesticide handling practices and self-perceived symptoms of acute pesticide poisoning was conducted using questionnaire-based interviews with 89 pesticide sprayers in Boeung Cheung Ek (BCE) Lake, Phnom Penh, Cambodia. The study showed that 50% of the pesticides used belonged to WHO class I + II and personal protection among the farmers were inadequate. A majority of the farmers (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 22 publications
11
64
2
1
Order By: Relevance
“…These results agree with [29], who reported that (92.0 %) of sample think pesticides can have a negative effect on the health. While the results in accordance with [30], who found that majority of the participant reported that exposure to pesticides hadn't an adverse effect on human health.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with [29], who reported that (92.0 %) of sample think pesticides can have a negative effect on the health. While the results in accordance with [30], who found that majority of the participant reported that exposure to pesticides hadn't an adverse effect on human health.…”
Section: Discussionsupporting
confidence: 92%
“…IPM emphasizes the importance of the growth of healthy crops and encourages natural pest control systems. It keeps the use of pesticides to a level that is affordable for the farmers and reduces the risk to humans and the environment while still yielding the expected outcome [4,7,13,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…This sample size was deemed sufficient to give a realistic picture of the situation on knowledge, attitude and practise among pesticide using farmers, based on experience from similar studies in other parts of the world [13,36]. The selection of farmers was done by convenience interviewing of 40 farmers who had been selected as representatives of farmer groups ,and those who showed up after being invited by a village farmer contact, a (snowballing) selection method not as good as random selection, but often used in studies in developing countries due to lack of person registers, appropriate directions of villagers and difficult accessibility.…”
Section: Participantsmentioning
confidence: 99%
“…Thus cotton pickers in non-Bt cotton fields reported more symptoms relating to cotton picking. Atreya [26] and Shetty et al [29] find most commonly symptoms including headache, weakness, dizziness, fever, blurred vision, and nausea/vomiting among farm workers in India. Rizwan et al [16] also find such type of symptoms among cotton pickers.…”
Section: Discussionmentioning
confidence: 99%